Nigeria’s Quest for Investments Relations from China: Prospects for Achieving Mutual Benefits - Rindap, Manko Rose; Warisu, Alli Oyesina; Gambo, Audu Nanven (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study assessed the prospects for achieving mutual benefits in the investment relations between Nigeria and China from 1999 to 2022. The investment relations involved execution of government contracts in the form of infrastructure such as roads, dams among others. The objectives of the study were to examine the nature and benefits of investment relations between Nigeria and China from 1999 to 2022. The methodology used was the explanatory design. The data were analysed through themes and content analysis. The findings revealed that Chinese investments in Nigeria was not beneficial to Nigeria in the area of technology transfer and equal opportunities for market access. This implied that the unequal relationship increased the dependency of the Nigerian economy on China